THE EFFECT OF COMMUNICATION AND MOTIVATION ON EMPLOYEE PERFORMANCE AT PT ESTIKA JASATAMA, CENTRAL JAKARTA - Marlinah, Henni (International Journal of Social and Management Studies, 2021)
This study aims to determine the effect of communication and motivation on employee performance at PT Estika Jasatama in Central Jakarta. This research method uses a quantitative and associative approach. The sample in this study were 60 people. Data collection techniques using questionnaires and data analysis techniques used multiple linear regression statistical analysis. Based on the research results, it is known: (1) communication has a significant effect on employee performance with the regression equation Y = 7.904 + 0.201 X1, the coefficient of determination is 76.2%, and hypothesis testing is obtained t count > t table or (2,966 > 2.002). Thus, H0 is rejected and H1 is accepted, meaning that there is a significant effect of the work environment on employee performance. (2) Motivation has a significant effect on employee performance with the regression equation Y = 7.904 + 0.517 X2¬ the value of the coefficient of determination is 76.2% and hypothesis testing is obtained t arithmetic > t table or (6.988 > 2.002). Thus, H0 is rejected and H2 is accepted, meaning that there is a significant effect of motivation on employee performance. (3) communication and motivation simultaneously have a significant effect on employee performance with the regression equation Y = 7.904 + 0.201 X1 + 0.517 X2 with the coefficient of determination adjusted r square is 0.76.2 or 76.2%, while the rest (100% - 76.2% = 23.8%) influenced or explained by other variables not included in this study. Based on the results of the F test, it is known that the calculated F value is 95,603 where the calculated F value is greater than the F table or 95,603 > 3.16. In addition, it is known that the significant value is less than 0.05 or 0.000 <0.05, then Ho is rejected and Ha is accepted, meaning that communication and motivation have a positive and significant effect on employee performance together.